2021
DOI: 10.3390/app11115293
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive Cruise Control for Cut-In Scenarios Based on Model Predictive Control Algorithm

Abstract: In a cut-in scenario, traditional adaptive cruise control usually cannot effectively identify the cut-in vehicle and respond to it in advance. This paper proposes an adaptive cruise control (ACC) strategy based on the MPC algorithm for cut-in scenarios. A finite state machine (FSM) is designed to manage vehicle control in different cut-in scenarios. For a cut-in scenario, a method to identify and quantify the possibility of cut-in of a vehicle is proposed. At the same time, a safety distance model of the cut-i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 30 publications
(29 reference statements)
0
15
0
Order By: Relevance
“…A study led by AAA [3] revealed that the functioning of the AEB system was unsuccessful under certain circumstances, such as children darting out, two pedestrians alongside the roadway when their silhouette was unclear from the background, or immediately after a right turn. The third category included other drivers and vehicles cutting in the front, causing the ACC system to malfunction with either late braking or excessive braking [10].…”
Section: Adas Limitationsmentioning
confidence: 99%
“…A study led by AAA [3] revealed that the functioning of the AEB system was unsuccessful under certain circumstances, such as children darting out, two pedestrians alongside the roadway when their silhouette was unclear from the background, or immediately after a right turn. The third category included other drivers and vehicles cutting in the front, causing the ACC system to malfunction with either late braking or excessive braking [10].…”
Section: Adas Limitationsmentioning
confidence: 99%
“…The experimental results show that the ACC cars improve the traffic stability and the dynamic road capacity. Chen et al [5] proposed an ACC strategy based on MPC algorithm for the cut-in scenarios, and established a safety distance model of the cut-in car. So that the ACC car can respond in advance and quickly switch the following target to the cut-in car when facing the cut-in car.…”
Section: Introductionmentioning
confidence: 99%
“…The MPC controller with linear time variation can improve the flexibility and stability of vehicle steering through multi-module allocation processing [29,30]. Adding adaptive to MPC can control the stability of vehicle tracking trajectory under complex operating conditions [31,32]. MPC combined with Gaussian function [33] and predictive following theory (PFT), respectively [34], such can improve vehicle driving comfort.…”
Section: Introductionmentioning
confidence: 99%